A study of frequency and pulses for stepper motor controller system by using programmable logic controller - Hassan, Suhaimi; Yusof, M S; Embong, Zaidi; Kamarudin, Q E; Haq, R H A; Ibrahim, M; Khairilhijra, K R; Marwah, O M F; Sa'ude, N; Ismon, Maznan; Madlan, M A (IOP Publishing, 2019)
The stepper motor movement process produced different frequency and pulses. This research explained about the frequency and pulses for the stepper motor movement by using Programmable Logic Controller (PLC) as research method. The study was done to find the suitable frequency and pulses for stepper motor movement by developing a prototype stepper motor controller system. The pulse frequency used did not affected the distance of moving load in the stepper motor operations. The increasing number of pulse frequency only will affect the time taken for the stepper motor to complete its operations. The result showed that number of pulse frequency at high operation was 5000 Hz. Pulse number reacted as a manipulated variable that affected both factor which is time taken of stepper motor operation and the distance of moving load.